2021
DOI: 10.1155/2021/8632823
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Integrin Alpha 6 in Nucleus Pulposus Cells in Response to High Oxygen Tension Protects against Intervertebral Disc Degeneration

Abstract: The destruction of the low oxygen microenvironment in nucleus pulposus (NP) cells played a critical role in the pathogenesis of intervertebral disc degeneration (IVDD). The purpose of this study was to determine the potential role of integrin alpha 6 (ITG α6) in NP cells in response to high oxygen tension (HOT) in IVDD. Immunofluorescence staining and western blot analysis showed that the levels of ITG α6 expression were increased in the NP tissue from IVDD patients and the IVDD rat model with mild degeneratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…1456 authors, 352 organizations, and 30 countries contributed to this field. Table 2 showed the top author with the most publications was Wang K ( n = 17) from Tongji Medical College ( Yin et al, 2021 ), the second was Shao ZW ( n = 16) from Tongji Medical College ( Chen S. et al, 2020 ), followed by Wang XY ( n = 15) from The Second Affiliated Hospital of Wenzhou Medical University ( Hu S. et al, 2021 ), Yang C ( n = 12) from Tongji Medical College ( Song et al, 2021 ), Zhang Y ( n = 12) from Third Military Medical University ( Xu et al, 2021 ). Of the 352 organizations, Huazhong University of Science Technology, Shanghai Jiao Tong University, Wenzhou Medical University, Zhejiang University, and Sun Yat Sen University had contributed 31, 21, 20, 15, and 12 publications, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…1456 authors, 352 organizations, and 30 countries contributed to this field. Table 2 showed the top author with the most publications was Wang K ( n = 17) from Tongji Medical College ( Yin et al, 2021 ), the second was Shao ZW ( n = 16) from Tongji Medical College ( Chen S. et al, 2020 ), followed by Wang XY ( n = 15) from The Second Affiliated Hospital of Wenzhou Medical University ( Hu S. et al, 2021 ), Yang C ( n = 12) from Tongji Medical College ( Song et al, 2021 ), Zhang Y ( n = 12) from Third Military Medical University ( Xu et al, 2021 ). Of the 352 organizations, Huazhong University of Science Technology, Shanghai Jiao Tong University, Wenzhou Medical University, Zhejiang University, and Sun Yat Sen University had contributed 31, 21, 20, 15, and 12 publications, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Compression induces oxidative stress, apoptosis, and ECM degradation in NP cells (Li et al, 2018). Oxidative damage can promote apoptosis and ECM degradation, which contribute to the development of IDD (Chen et al, 2019;Xu et al, 2021). Therefore, for the successful application of NP tissue engineering, we focused on preventing compression-induced oxidative stress and subsequent NP cell apoptosis and ECM degradation (Sun et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of ITG-α6 expression by HOT helps maintain NP tissue homeostasis through the interaction with HIF-1α (Kim et al, 2021;Zheng et al, 2021). It was found that the expression levels of ITG-α6 were increased in NP tissue of IVD degeneration patients and IVD degeneration rat model with mild degeneration, which could produce the above-mentioned effects to protect NP cells from hyperoxia (Xu et al, 2021). In addition, MnO 2 particles can protect Langerhans islet cells (Tootoonchi et al, 2017).…”
Section: Anti-inflammatory Effect Of Mno 2 Microspheres In Vivomentioning
confidence: 97%